PENGARUH BEBAN OPERASIONAL PENDAPATAN OPERASIONAL DAN NON PERFORMING LOAN TERHADAP RETURN ON ASSET PADA PT BANK RAKYAT INDONESIA TBK PERIODE 2012-2024 - Pratiwi, Rindis; Hermawan, Hengki (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2025)
The purpose of this study is to determine the effect of operating expenses, operating income, and non performing loans on return on assets at PT Bank Rakyat Indonesia Tbk for the period 2012-2024. This study uses a quantitative method with a sample consisting of Bank Rakyat Indonesia Tbk's financial statements for the period 2012- 2024. The data analysis techniques used are: Normality test, Multicollinearity test, Autocorrelation test, Heteroscedasticity test, Multiple Linear Regression test, Multiple Correlation Coefficient test, Coefficient of Determination Analysis test, t- test, and f-test. Based on the t-test results, the Operational Expense to Operational Income Ratio (BOPO) has a significant effect on the Return on Assets (ROA) at PT Bank Rakyat Indonesia Tbk for the period 2012-2024, as evidenced by the calculated t-value of -9,941 > the critical t-value of 2.228, and the significance level of 0.000 < 0.05. Based on the results of the t-test, Non Performing Loan (NPL) has a significant effect on Return on Assets (ROA) at PT Bank Rakyat Indonesia Tbk for the period 2012-2024, as evidenced by the t-value of 4,402 > t-table 2.228, and the significant value of 0.001 < 0.05. Based on the results of the F-test, the Operational Expense to Operational Income Ratio (BOPO) and Non Performing Loan (NPL) significantly influence the Return on Assets (ROA) at PT Bank Rakyat Indonesia Tbk for the period 2012-2024, as evidenced by the calculated F-value of 51,191 and the table F-value of 4,10 with a significance level of 0.000 < 0.05.